2013
DOI: 10.1161/jaha.113.000455
|View full text |Cite
|
Sign up to set email alerts
|

Intake of Dietary Phylloquinone and Menaquinones and Risk of Stroke

Abstract: BackgroundDietary vitamin K intake is thought to decrease the risk of cardiovascular disease (CVD) by reducing vascular calcification, although vitamin K is also involved in coagulation. Studies investigating the association between phylloquinone intake and risk of stroke are scarce, and the relation with menaquinones has not been investigated to date.Methods and ResultsWe investigated the association between intake of phylloquinone and menaquinones and stroke in a prospective cohort of 35 476 healthy subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 46 publications
4
35
1
1
Order By: Relevance
“…Another nutrient present in cheese is menaquinone-n, which was inversely associated with CVD risk in several previous cohort studies (29,30) . However, a previous study in the EPIC-NL cohort has found no association between menaquinone-n intake and stroke incidence (31) , so we find it very unlikely that this micronutrient explains our association. Moreover, the present results are not consistent with those of recent observational studies that reported no consistent associations between cheese intake and stroke incidence (11,32,33) , and a previous analysis in the EPIC-NL cohort has shown no association between cheese intake and stroke incidence (7) .…”
Section: Discussioncontrasting
confidence: 73%
“…Another nutrient present in cheese is menaquinone-n, which was inversely associated with CVD risk in several previous cohort studies (29,30) . However, a previous study in the EPIC-NL cohort has found no association between menaquinone-n intake and stroke incidence (31) , so we find it very unlikely that this micronutrient explains our association. Moreover, the present results are not consistent with those of recent observational studies that reported no consistent associations between cheese intake and stroke incidence (11,32,33) , and a previous analysis in the EPIC-NL cohort has shown no association between cheese intake and stroke incidence (7) .…”
Section: Discussioncontrasting
confidence: 73%
“…Despite promising results in pre-clinical animal models, clinical trials haven't demonstrated any benefit in man [43][44][45][46]. Vitamin K supplementation is safe in human and interventional studies are needed to determine if vitamin K supplementation could prevent diabetic peripheral neuropathy [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…No side events were recorded in a Japanese trial of 2185 postmenopausal osteoporotic women receiving 45 mg menatetrenone for 3 years [ 10 ]. Vitamin K intake was not associated with stroke risk in a prospective cohort of 35 476 healthy subjects [ 11 ]. Another potential problem relates to the vitamin K-dependent carboxylation of osteocalcin, also termed Bone Gla protein [ 12 ].…”
Section: Background and Objectivesmentioning
confidence: 99%